2019
DOI: 10.3390/cryst9080379
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-Ray Crystal Structure, Hirshfeld Surface Analysis, and Molecular Docking Study of Novel Hepatitis B (HBV) Inhibitor: 8-Fluoro-5-(4-fluorobenzyl)-3-(2-methoxybenzyl)-3,5-dihydro-4H-pyrimido[5,4-b]indol-4-one

Abstract: A method for the synthesis of 8-fluoro-5-(4-fluorobenzyl)-3-(2-methoxybenzyl)-3,5-dihydro-4H-pyrimido [5,4-b]indol-4-one has been developed and the electronic and spatial structure of a new biologically active molecule has been studied both theoretically and experimentally. The title compound was crystallized from acetonitrile and the single-crystal X-ray analysis has revealed that it exists in a monoclinic P2 1 /n space group, with one molecule in the asymmetric part of the unit cell, a = 16.366(3) Å, b = 6.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Molecular docking is an emerging topic for pharmaceutical crystal study. Ivashchenko et al reported the crystal structure of a new biologically active molecule, which was also investigated as a new inhibitor of hepatitis B in a molecular docking study [9]. This substance has in vitro nanomolar inhibitory activity against the hepatitis B virus (HBV).…”
Section: Dear Colleaguesmentioning
confidence: 99%
“…Molecular docking is an emerging topic for pharmaceutical crystal study. Ivashchenko et al reported the crystal structure of a new biologically active molecule, which was also investigated as a new inhibitor of hepatitis B in a molecular docking study [9]. This substance has in vitro nanomolar inhibitory activity against the hepatitis B virus (HBV).…”
Section: Dear Colleaguesmentioning
confidence: 99%
“…Heterocyclic homologues of 2H-1,2,6-thiadiazine-1,1-dioxides are inhibitors of human cytomegalovirus (Martínez et al, 2003), Cruzi triposome (Á lvarez et al, 2010) and diuretics (Goya et al, 1992). In a continuation of our efforts to obtain new HBV inhibitors for the treatment and prevention of human HBV infections (Ivachtchenko et al, 2019;Ivashchenko et al, 2019;Kovalenko et al, 2019), we initiated the design, synthesis, and anti-hepatitis B virus activity testing of the new 2H-1,2,6thiadiazine 1,1-dioxide derivative, ethyl 5-methyl-1,1-dioxo-2-{[5-(pentan-3-yl)-1,2,4-oxadiazol-3-yl]methyl}-2H-1,2,6-thiadiazine-4-carboxylate (3).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The biological activity of compound 3 was studied using an experimental in vitro hepatitis B virus infection model based on human hepatoma line HepG2 stably transfected with the NTCP gene [42]. This model, which maintains a full virus replication cycle, was developed in our laboratories for identification of viral entry inhibitors, promising candidates to prevent development of resistant HBV forms [43]. The title molecule 3 demonstrated 86% inhibition of HBV replication (in 10 µM concentration) in this model.…”
Section: Anti-hepatitis B Virus (Hbv) Activitymentioning
confidence: 99%